Rancang Bangun Pengendali Peralatan Listrik Rumah Tangga Menggunakan Sistem DTMF Handphone - Rosdaria Ambarita (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2022)
Changes in human life patterns today, many due to the rapid development of technology that many provide all forms of convenience in the use of devices or tools that are directly related to human life. Therefore, developments in the field of electrical technology that is analog or digital. Electrical equipment in our homes can be controlled if we are always close to the electrical equipment. These are some of the shortcomings of controlling household electrical appliances that exist today. It is necessary to control electrical equipment using a mobile DTMF system that can overcome these problems.